Development of a computational vehicle dynamics model for a racing car (2020)
In this document, the first version of a computational model of the Salamandra racing car, built in OpenModelica, is presented. With this model, the behavior of the car in the longitudinal dynamics was simulated through the modeling of all the subsystems that play a role in the straight-line performance. Additionally, a 3-parameter shifting logic was implemented in the transmission of the vehicle to enhance its behavior on inclined roads. Validation with information from the manufacturer and theory showed, that the developed model is able to accurately simulate the behavior of the car in longitudinal motion